Synthesis of Clitocybin A, B and C and their Biological Evaluation for Antioxidant Activities. (7th July 2019) - Lee, Sangku; Kim, Jae Nyoung; Hyun, Jin Won; Yoo, Ick‐Dong; Kim, Bo Yeon
Abstract : Clitocybin A, isolated from the culture broth of mushroom Clitocybe aurantiaca, showed various biological activities such as cell death inhibition effects, anti‐wrinkle effects, aortic smooth muscle cell proliferation inhibition effects. In an effort to further develop this promising compound toward a potent antioxidant, we have modified the structure of clitocybin A by changing the number of free phenolic hydrogen in isoindolinone moiety. In this paper, clitocybin A and its analogues, clitocybin B and C were synthesized and their antioxidant activities were evaluated. Clitocybin A possessing two phenolic hydrogens in isoindolinone moiety of clitocybin A analogues showed more potent radical scavenging activity than clitocybin B possessing one phenolic hydrogen. In inhibition of cellular DNA damage in H2O2treated cells, clitocybin C lacking free phenolic hydrogen in isoindolinone moiety showed more potent activity than clitocybin A possessing two phenolic hydrogens.Among the tested compounds, clitocybin A only showed dose‐dependently HNE inhibitory activity with an IC50 value of 78.8 uM. The presence of free phenolic hydrogens inisoindolinone moiety of clitocybin A analogues plays an important role in antioxidant activities. Abstract :